NOBIN-based chiral phosphite-type ligands and their application in asymmetric catalysis. Issue 33 (12th August 2015) - Gavrilov, Konstantin N.; Shiryaev, Alexei A.; Zheglov, Sergey V.; Bochelyuk, Marina S.; Chuchelkin, Ilya V.; Tafeenko, Viktor A.; Chernyshev, Vladimir V.; Zamilatskov, Ilya A.; Mikhel, Igor S.
Graphical abstract: Abstract: P ∗ -Monodentate diamidophosphite and diastereomeric P, N -containing phosphite ligands have been synthesized from enantiomerically pure N -Bn-NOBIN and used as asymmetric inductors in Pd-catalyzed allylic substitution and Cu-catalyzed conjugate addition reactions. The best results (up to 93% ee) were obtained for the Pd-catalyzed allylic alkylation of ( E )-1, 3-diphenylallyl acetate with 1-cyclohexenylpyrrolidine. The reactions of P, N -containing ligands with Pd(COD)Cl2 at molar ratios of L/M = 1 and 2 were studied using 1 H, 13 C, and 31 P NMR spectroscopy as well as HRESI mass spectrometry, showing the trans -PdCl2 L2 complex was the only product.